Influence of inter-fin base length on thermal performance of free hanging horizontal base heat sinks. (5th September 2016) - Schmid, Gerd; Yang, Li-Hao; Yang, Tai-Her; Chen, Sih-Li
Graphical abstract: Highlights: A total of 55 experiments are conducted and used to validate the numerical model. Inter-fin base length influences optimal fin orientation and spacing of heat sinks. The thermal resistance is reduced up to 36.7% for same heat sink base area. Nusselt number correlations based on the numerical results are proposed. The findings of the study are useful for high-power LED lighting applications. Abstract: In the present study we analyzed the effect of varying the inter-fin base length of free hanging rectangular heat sinks with a central heat source cooled by natural convection. Typical applications for this type of heat sink are modern high-power LED street and flood lights. We compared heat sinks with two different fin orientations, one with the fins along the longer base side (Type A) and one along the shorter base side (Type B). The parameters in this study are the fin spacing, the power input, the base length, and the inter-fin base length. A numerical parametric study using ANSYS Icepak with a total of 189 different geometries was carried out. For a closed base with outer dimensions of 18 cm × 40 cm Type B can achieve an about 15% better thermal performance than Type A. For shorter inter-fin base lengths the thermal resistance of Type A is significantly lowered by up to 36.7%, while for Type B the maximum reduction is just 9.7%. It was further shown that the inter-fin base length greatly influences the optimal fin spacing. For the complete data Nu-correlations including a parameter for the inter-fin base length were developed.